All you need to know on a species that inspired myths and legends: ecology, behaviour, evolution, conservation and curiosities on the Little Owl (Avocetta, 2025)
Review of Van Nieuwehuyse D., van Harxen R. and Johnson D.H., 2023. The Little Owl. Population Dynamics, Behavior and Management of Athene noctua. 2nd Ed. Cambridge University Press 616 pp.